Unilateral Urogenital Disontogeny in a Dog - Adolfo Maria Tambella; Stefano Martin; Matteo Cerquetella; Daniele Spaziante; Angela Palumbo Piccionello; Andrea Marchegiani; Umberto Faccenda; Giacomo Rossi (Case Reports in Veterinary Medicine)
The purpose of this report was to describe an uncommon congenital anomaly in a dog. An 8-year-old, mixed-breed, male dog, was referred because of progressive difficulties on defecation. A complete diagnostic work-up (hematological analysis, radiology, ultrasound, and computed tomography), followed by surgery and histopathology, allowed us to diagnose the condition as unilateral urogenital disontogeny. The disorder was characterized by unilateral anomalies of the urinary tract (ectopic and dilated hydroureter, hydronephrosis, and renal dysplasia) associated with ipsilateral anomalies of the genital system (partial permanence of the duct of Wolff evolved into an epididymal-like structure and testicular agenesis). En bloc surgical excision of the complex of urogenital anomalies was performed with no complications during or after surgery. Surgery was considered to be effective in this dog since he no longer showed clinical signs of illness.